Comparison between the Correlations of Retinal Nerve Fiber Layer Thickness Measured by Spectral Domain Optical Coherence Tomography and Visual Field Defects in Standard Automated White-on-White Perimetry versus Pulsar Perimetry. (8th October 2017) - Alnawaiseh, Maged; Hömberg, Lisann; Eter, Nicole; Prokosch, Verena
Abstract : Purpose. To compare the structure-function relationships between retinal nerve fiber layer thickness (RNFLT) and visual field defects measured either by standard automated perimetry (SAP) or by Pulsar perimetry (PP). Materials and Methods. 263 eyes of 143 patients were prospectively included. Depending on the RNFLT, patients were assigned to the glaucoma group (group A: RNFL score 3–6) or the control group (group B: RNFL score 0–2). Structure-function relationships between RNFLT and mean sensitivity (MS) measured by SAP and PP were analyzed. Results. Throughout the entire group, the MS assessed by PP and SAP correlated significantly with RNFLT in all sectors. In the glaucoma group, there was no significant difference between the correlations RNFL-SAP and RNFL-PP, whereas a significant difference was found in the control group. Conclusions. In the control group, the correlation between structure and function based on the PP data was significantly stronger than that based on SAP.